Pollution, shadow economy and corruption: Theory and evidence - Amit K. Biswas; Mohammad Reza Farzanegan; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2011)
We study how the shadow economy affects pollution and how this effect depends on corruption levels in public administration. Production in the shadow economy allows firms to avoid environmental regulation policies; a large informal sector may be accompanied by higher pollution levels. Our theoretical model predicts that controlling the levels of corruption can limit the effect of the shadow economy on pollution. We use panel data covering the period from 1999-2005 from more than 100 countries to test this theoretical prediction. Our estimates confirm that the relationship between the shadow economy and the levels of pollution are dependent on the levels of corruption. Our results hold when we control for the effects of other determinants of pollution, time varying common shocks, country-fixed effects and various additional covariates.
Keywords: Q53; Q56; Q58; 330; environmental pollution; shadow economy; corruption; panel data